Design, Fabrication, and Performance Evaluation of Open Raceway Ponds for the Cultivation of Chlorella vulgaris Beijerinck in the Philippines. - Matanguihan, Anna Elaine
Two pilot-scale open raceway pond systems were designed and fabricated in the University of the Philippines Los Baños (UPLB) for the cultivation of Chlorella vulgaris Beijerinck to observe the biomass productivity of the alga in an open condition in the Philippines. One design was an oval track with a middle island, while the other was a multi-stage raceway pond (MSRP) consisted of several sections separated by baffles. The pond designs aimed to accommodate 1,000 L of culture. The nutrient media used was composed of urea, NPK (16-20-0), FeCl3, and Na2EDTA ? a locally formulated medium that sustains the growth of the species. Paddlewheel was installed to provide mixing, which was turned on during the daytime, while aeration was continuously supplied through perforated air-distributor PVC pipes installed on the pond floor. Only natural light was utilized, and no lighting was provided during the night. The growth rate was generated by monitoring the biomass concentration in the pond through spectrophotometry at 425 nm, where optical density and biomass concentration relationship was initially established. Using the equation for first-order kinetics and taking the points from the exponential phase, the specific growth rate of Chlorella obtained from the oval raceway pond was computed to be 0.007308 h?1 with doubling time of 94.84 h. The biomass productivity rate was computed to be 308.49 g/m3-d or equivalent to 63.24 g/m2-d. On the other hand, the MSRP obtained a specific growth rate of 0.003389 h?1 with a doubling time of 204.55 h and equivalent biomass productivity of 302.19 g/m3-d or 60.44 g/m2-d. The biomass productivity obtained is comparable, even superior to other commercial open pond cultivation using C. vulgaris.